Glutathione S-transferase gene polymorphisms and risk of nasal or colorectal polyposis. Issue 1 (25th January 2019) - Zhang, Yonglan; Zhang, Haichao; Lin, Peng; Zhang, Guimin
Abstract : We observed inconsistent conclusions regarding the genetic role of glutathione S-transferase gene polymorphisms, including glutathione S-transferase M1 ( GSTM1 ), glutathione S-transferase T1 ( GSTT1 ) present/null, and glutathione S-transferase pi (GSTP1 ) Ile105Val polymorphisms, in the susceptibility to nasal or colorectal polyposis (NP or CP). Thus, we aimed to perform a meta-analysis to comprehensively evaluate this association by applying Stata/SE software. After the heterogeneity assumption, Mantel–Haenszel statistics were used to obtain the odds ratio (OR), 95% confidence interval (95% CI) and P -value of the association test ( PA ). We obtained a total of 235 articles by searching online databases. After screening, ten eligible case–control studies were finally enrolled in our meta-analysis. For the meta-analysis of the GSTT1 gene under present versus null, we observed a decreased risk of NP [OR = 0.65; PA =0.018], but not CP. In addition, we did not detect any evident association between the GSTM1 present/null polymorphism and NP or CP risk. For the meta-analysis of the GSTP1 Ile105Val polymorphism, compared with controls, an increased risk of NP cases was detected under the models of Val versus Ile (OR = 1.36; PA =0.027), Ile/Val versus Ile/Ile (OR = 1.70; PA =0.011) and Ile/Val+Val/Val versus Ile/Ile (OR = 1.65; PA =0.010). In conclusion, the null genotype of the GSTT1 polymorphism may be linked to an increased susceptibility to NP, whereas the Ile/Val genotype of the GSTP1 Ile105Val polymorphism may be associated with a decreased risk of NP.